Increasing the aperture of x-ray mosaic lenses by freeze drying. (8th June 2015) - Koch, F; Marschall, F; Meiser, J; Márkus, O; Faisal, A; Schröter, T; Meyer, P; Kunka, D; Last, A; Mohr, J
Abstract: Point focus x-ray mosaic lenses are limited in aperture by the aspect ratio that can be reached in the micro fabrication process. In lithography based micro fabrication processes, which are used to fabricate the lens pillar structures, the achievable aspect ratio is restricted by structure collapse due to capillary forces which occur during drying after development. Capillary forces can be avoided by freeze drying, hence avoiding the direct phase change from liquid to gas. Substituting conventional drying by freeze drying using cyclohexane at a temperature of −10 °C, we could increase the achievable aspect ratio for the triangular pillar structures with edge length of 10 to 45 µ m of the x-ray mosaic lenses by up to a factor of 2.2 with no further changes in process, material or structural geometry. A maximum aspect ratio of 30 was achieved for pillars with 10 µ m edge length. The process can readily be employed to other structures or lithography techniques.